Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 45 x 76 + 90 x 12
= 45 x 76 + 45 x 2 x 12
= 45 x 76 + 45 x 24
= 45 x ( 76 + 24 )
= 45 x 100
= 4500
b) 2 x 31 x 12 + 4 x 6 x 69
= 24 x 31 + 24 x 69
= 24 x ( 31 + 69 )
= 24 x 100
= 2400
c) 36 x 28 + 36 x 82 + 64 x 69 + 64 x41
= 36 x ( 28 + 82 ) + 64 x ( 69 + 41 )
= 36 x 110 + 64 x 110
= 110 x ( 36 + 64 )
= 110 x 100
= 11 000
d) 156 ( x + 61) = 82
=> x + 61 = \(\frac{82}{156}\)
=> x + 61 = \(\frac{41}{78}\)
=> x = \(\frac{41}{78}\)- 61
=> x = \(\frac{-4717}{78}\)
45 x 76 + 90 x 12 = 45 x 76 + 45 x 2 x 12
= 45 x 76 + 45 x 24
= 45 x (76 + 24)
= 45 x 100
= 4500
b) 2 x 31 x 12 + 4 x 6 x 69 = 62 x 12 + 2 x 12 x 69
= 62 x 12 + 138 x 12
= (62 + 138) x 12
= 200 x 12 = 2400
a,\(\left(x-15\right):50+22=24\)
\(< =>\frac{\left(x-15\right)}{50}=2< =>x-15=100\)
\(< =>x=100+15=115\)
b,\(42-\left(2x+32\right)+12:2=6\)
\(< =>42-2x-32=0\)
\(< =>10-2x=0< =>x=\frac{10}{2}=5\)
Làm nốt :
c) \(134-2\left\{156-6\cdot\left[54-2\cdot\left(9+6\right)\right]\right\}\cdot x=86\)
=> 134 - 2{156 - 6 . [54 - 2 . 15]} . x = 86
=> 134 - 2{156 - 6 . [54 - 30]} . x = 86
=> 134 - 2{156 - 6. 24} . x = 86
=> 134 - 2{156 - 144} . x = 86
=> 134 - 2.12 . x = 86
=> 134 - 24 . x = 86
=> 24.x = 48
=> x = 2
Bài 2 : a) 120 : [21 - (4x - 4)] = 23.3
=> 120 : [21 - (4x - 4)] = 8.3
=> 120 : [21 - (4x - 4)] = 24
=> 21 - (4x - 4) = 5
=> 4x - 4 = 16
=> 4x = 20
=> x = 5
b) 3.[205 - (x - 9)] - 486 = 0
=> 3.[205 - (x - 9)] = 486
=> 205 - (x - 9) = 162
=> x - 9 = 205 - 162 = 43
=> x = 43 + 9 = 52
c) 204 - 2{200 - 5.[64 - 2.(11 + 6)]} . x = 4
=> 204 - 2{200 - 5.[64 - 2.17]} . x = 4
=> 204 - 2{200 - 5 .[64 - 34]}.x = 4
=> 204 - 2{200 - 5.30} . x = 4
=> 204 - 2{200 - 150}.x = 4
=> 204 - 2.50 . x = 4
=> 2.50.x = 200
=> 100.x = 200
=> x = 2
\(a:\)\(64.6+81.4+17.6\)
\(=\left(64+17\right).6+81.4\)
\(=81.6+81.4\)
\(=81.\left(6+4\right)\)
\(=81.10\)
\(=810\)
a) ( -2 ).8. ( 5 )2 .( -3 )2.( -5 )
= (-2). 8. 25. (-9). (-5)
= -18000
b) ( 256 – 197) – ( 185 + 156 – 197 )
= 256 -197 -185 -156 +197
= (256-156) + (-197+197) -185
= 100 - 185
= -85
c)18 . 13 – 3 . 6 . 10
= 3.6.13 - 3.6.10
= 3.6.(13-10)
= 18 . 3
= 54
d) 125. 64 + (- 64) . 55 + 60. (- 164)
= 125.64+ 64. (-55) + 60. [(-100) + (-64)]
= 125.64 + 64.(-55)+ 60.(-100)+60.(-64)
= [125+ (-55) + (-60)] . 64 + (-6000)
= 10.64 + (-6000)
= 640+(-6000)
= -5360
a) (x + 23) - 14 = 11
=> x + 23 - 14 = 11
=> x + 9 = 11
=> x = 11 - 9 = 2
b) 2.x + 13 = 43
=> 2.x = 43 - 13
=> 2.x = 30
=> x = 15
c) 2(x - 1) - 156 = 196
=> 2x - 2 = 352
=> 2x = 354
=> x = 177
3(134 - x) + 1 = 211
=> 3(134 - x) = 210
=> 134 - x = 70
=> x = 134 - 70 = 64
h) 156 - 2(x + 2) = 128
=> 2(x + 2) = 156 - 128 = 28
=> x + 2 = 28 : 2
=> x + 2 = 14
=> x = 12
3.x-1452+156=879
3.x-1452=879-156
3.x-1452=723
3.x=723+1452
3.x=2175
x=2175:3
x=725
156-(x-3)=64
=>x-3=156-64=92
=>x=92+3=95
=>x=95
(x-3)=156-64
x-3=92
x=92+3
x=95
Nhớ k cho mình nha